Performance evaluation of TCP Vegas versus different TCP variants in homogeneous and heterogeneous wired networks - B. S., Yew; Ong, Bi Lynn; R. Badlishah, Ahmad, Prof. Madya Dr. (World Academy of Science, Engineering and Technology (WASET), 2011)
Link to publisher's homepage at http://www.waset.org/